Strengthening The Soul to Preserve Culture: Hangasa Juice Therapy on Sleep Quality and Anxiety to Prevent Psychosocial Mental Emergencies in Class IIB Correctional Centre, Banjar City - Reni Hertini; Siti Rohimah; Asri Aprilia Rohman (LPPM Universitas Harapan Bangsa, 2024)
Correctional Inmates (WBP) in prisons are vulnerable to experiencing anxiety and sleep disorders due to environmental pressure. This study tested the effectiveness of hangasa juice, a herbal-based non-pharmacological intervention, in reducing anxiety and improving sleep quality in inmates at Class 2B Prison in Banjar City. A quantitative approach with a quasi-experimental one-group pretest-posttest design was used, involving WBP as the sample. The results show that the significance of the pre-test and post-test results on anxiety levels is 0.331>0.05 and the results of sleep quality show that the significance of the pre-test and post-test results is 0.199>0.05 collected using the PSQI and SAS/SRAS questionnaires. The results showed a decrease in anxiety levels and an increase in sleep quality after the intervention, although not statistically significant. These findings indicate the potential of hangasa juice in overcoming anxiety and improving sleep quality, in line with previous research that research results show that hangasa contains flavonoids, alkaloids, tannins and essential oils, which have biological activity that is good for health. Extracts from Hangasa have significant antioxidant activity. These properties are in line with the antioxidant and antimicrobial properties of the essential oils contained in this plant. So this research opens up opportunities for further research with a stronger design to test its effectiveness and explore its mechanism of action.